2013
DOI: 10.3109/02813432.2013.824156
|View full text |Cite
|
Sign up to set email alerts
|

“I'm Dr JekyllandMr Hyde”: Are GPs’ antibiotic prescribing patterns contextually dependent? A qualitative focus group study

Abstract: ObjectiveTo explore factors and circumstances contributing to prudent antibiotic prescribing for respiratory tract infections in primary care.DesignTwo focus groups representing rural and urban areas. A semi-structured interview guide with open-ended questions and an editing analysis style was used. They were examined to identify meaning units that were sorted into categories in an iterative process throughout the analysis.SettingPrimary health care in two counties in southern Sweden.SubjectsTwo groups includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Fear and self-interest of physicians are confirmed as factors that influence the prescribing of antibiotics in other similar studies (24)(25)(26)(27). In our study, it was also shown that physicians have fear of treating patients who are emergent cases and who have another doctor as referring physician.…”
Section: Discussionsupporting
confidence: 83%
“…Fear and self-interest of physicians are confirmed as factors that influence the prescribing of antibiotics in other similar studies (24)(25)(26)(27). In our study, it was also shown that physicians have fear of treating patients who are emergent cases and who have another doctor as referring physician.…”
Section: Discussionsupporting
confidence: 83%
“…This was supported by the results, which showed that some of the HCPs lacked pharmacological knowledge about ABs. Hence, physicians in other countries appear to disagree more often with their patients when prescribing ABs, and they then try to negotiate with patients to find a solution, than what was observed in this study [22]. …”
Section: Discussionmentioning
confidence: 64%
“…Despite the fact that physicians and community pharmacists are the legal and professional gatekeepers to patients’ access to ABs, the influence of patients on for example physicians’ AB prescribing practices has been demonstrated in previous studies [7, 22]. Therefore, it was considered important to incorporate these groups in this study.…”
Section: Methodsmentioning
confidence: 99%
“…22 Qualitative research conducted in other countries has demonstrated similar findings to the current study. [27][28][29][30] Evidence suggests that GP prescribing decisions depend on the interaction with the patient and other influencing factors, such as GP characteristics and continuity of care, mutual trust, and flexibility with the patient. 30 GPs interviewed for the current study also saw prescribing as a negotiation tool; however, some did not agree with the delayed prescribing approach as they found it to be contradictory and felt patients ought to have less autonomy.…”
Section: Main Findingsmentioning
confidence: 99%
“…30 GPs found that having consistencies in prescribing behaviours throughout the primary care centre, as well as the use of local professional discussions and exchange of experience that facilitates their prescribing practice. This emphasises the call for wider policy implementation and open discussion within and between practices within CCGs, to enable a more consistent rate of prescribing around the UK.…”
Section: Main Findingsmentioning
confidence: 99%